EP-210 Routine colonoscopy after acute diverticulitis – appraising an age-old practice. (9th August 2022) - Elsaid, Nada; Paxton, Benjamin; Ismail, Adam; Oshowo, Ayo
Abstract: The standard of care for patients with diverticulitis is to perform a colonoscopy following resolution of the acute episode, to exclude occult malignancy. But how often does malignancy masquerade as diverticulitis? Further, when deciding whether or not to investigate these patients, there does not appear to be a consensus for those who have had a previous colonoscopy confirming diverticulosis only. We examined this cohort to assess the outcomes of their endoscopic screening. Historically, tests, including barium studies, yielded a lower sensitivity but since the advent of CT colonography, the results are more accurate with the added benefit of reduced procedure-related morbidity and burden on the NHS. We consider whether routine endoscopic colonic evaluation post diverticulitis should, to all intents and purposes, become obsolete. A total of 34 patients (identified from a series of 457) were coded with a diagnosis of diverticulitis between September and December 2021. Of these, 21 underwent subsequent endoscopic evaluation post inflammatory episode. 0 patients had cancer. 2 patients had tubular adenomatous polyps, displaying low grade dysplasia. Interestingly, technical difficulty and/or poor patient tolerance meant that 4 of these patients underwent a flexible sigmoidoscopy only. 1 patient developed diverticulitis a month after their scope. 2 patients had repeat colonoscopies within 2 years, the indication being diverticulitis. The authors acknowledge that the sample used is small and robust conclusions could not be drawn thus far. Our aim is to evoke interest in the reader with this study serving as a precursor to a larger project that is underway.